New pearl millet hybrids at IARI - Singh, S. P.; Satyavathi, C. Tara; S, Mukesh Sankar (Indian Farming, 2018)
The Indian Agricultural Research Institute, New Delhi has developed hybrids, open pollinated varieties, seed parents and male parents pollinators/restorers) of pearl millet; and helped India to become largest producers of this crop [ both in terms of area (7.8 million ha) and production (2.5 million tonne)] with an average productivity of 1,270 kg/ha.